Association between daily screen time and risk of stroke among middle-aged and elderly people: research based on China health and nutrition survey - Ren, Yaxin; Sun, Kejuan; Rong, Yueqing; Song, Shiming; Zhai, Yijing; Miao, Junjie; Shi, Hongmei; Xue, Hongmei; Li, Zengning (Frontiers in Sports and Active Living, 2023)
Background We aimed to explore the independent associations between screen time and the risk of stroke among Chinese adults based on the China Health and Nutrition Survey (CHNS). Methods Data on Chinese adults aged older than 40 years from the CHNS in during 2004–2009 were selected. A total of 4,587 individuals were included in 2009, including screen time and the risk of stroke. Simultaneously, we traced the previous screen time to 2004 for those with outcome measures in 2009 (n = 2,100). Basic information, lifestyle, and screen behavior were obtained through face-to-face interviews and self-completed questionnaires. Anthropometric data collected included blood pressure, body weight, height, hip circumference, and waist circumference. Fasting blood was obtained for measurements of lipid and glucose levels. Cross-sectional analysis and cohort analysis were both performed using multivariate logistic regression. Results Of all participants, 3,004 (65.49%) participants spent more than 2 h per day on screen time. Taking the men who spent less than 2 h on screen per day as reference, the crude odds ratio (OR) of the high risk of stroke was 1.53 [95% confidence interval (CI), 1.20–1.95] for the men who spent 2–3 h per day on screen and 2.37 (95% CI, 1.78–3.16) for the men who spent more than 3 h per day on screen. This difference remained significant after adjusting for confounding factors. No association was observed among women. However, in the cohort analysis with screen time in 2006 as the independent variable, the association between screen time and stroke risk was found both in men [OR, 1.83 (95% CI, 1.19–2.82)] and women [OR, 1.48 (95% CI, 1.10–1.99)]). Conclusion We found that the high screen time was associated with an increased stroke risk, which was pronounced in men, warranting a universal need to limit screen time in order to improve health.